Marine Reserves Do they bring net Benefits to Economies? - Tyl, Michal; Hitzgerová, Gabriela, 1944-; Tofan, Lukáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2007)
Although more than 1300 marine reserves have already been established around the world, they still present a relatively new tool for environmental conservation and fisheries management. In accordance with this new approach towards marine protection, conservationists currently call for rapid establishment of a reserve network, which would encompass 10% to 30% of the oceans. Representative habitats from coastal areas as well as high seas would be included. Such a network should serve as a haven for marine species, ensuring their sustainability and aiding them to recover from fishery pressure. Furthermore, reserves are expected to enhance yields to the fishing industry through spillover and larval export. The paper attempts to determine, whether and under which conditions do marine reserves bring net benefits to economies.
Vedoucí práce: Gabriela Hitzgerová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2007
Rok obhajoby 2007
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses